Additive Manufacturing of Metal Objects

By using a slurry with metal precursors that match the resin's refractive index and have lower extinction coefficients, the method enhances curing depth and mechanical strength in additive manufacturing of three-dimensional metal objects, producing objects with improved microstructures.

JP7607683B2Active Publication Date: 2024-12-27ADMATEC EURO
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023001198
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-05-10
Filing Date
2023-01-06
Publication Date
2024-12-27
Estimated Expiration
2038-05-09

AI Technical Summary

Technical Problem

Existing additive manufacturing methods for three-dimensional metal objects face limitations in curing depth and mechanical strength due to the high refractive index and extinction coefficient of metal particles, leading to shallow cure depths and potential defects in the final product.

Method used

A slurry comprising a polymerizable resin, photoinitiator, and a mixture of metal particles and metal precursors is used, where the metal precursors have a refractive index closer to the resin and lower extinction coefficient, allowing for increased curing depth and improved mechanical strength.

Benefits of technology

The method achieves a deeper cure depth and produces three-dimensional metal objects with sufficient mechanical strength, resulting in stress-free, highly homogeneous, and fine-grained microstructures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607683000002
    Figure 0007607683000002
  • Figure 0007607683000003
    Figure 0007607683000003
  • Figure 0007607683000001
    Figure 0007607683000001
Patent Text Reader

Abstract

A method and energy beam curable slurry for the additive manufacturing of three-dimensional metal objects with increased depth of cure based on indirect stereolithography or related methods is provided. The slurry comprises: a) 2-45 wt % polymerizable resin; b) 0.001-10 wt % photopolymerization initiator; and c) 55-98 wt % mixture of metal-containing compounds, the mixture comprising 5-95 wt % metal particles and 5-95 wt % metal precursors, based on the weight of the mixture. An additive manufacturing method also includes the steps of: constructing a green body of the metal particles and metal precursors using the slurry according to the invention; removing the organic binder from the green body to obtain a Brownian body; and optionally converting any remaining metal precursors to the corresponding metals to obtain a three-dimensional metal object. In another aspect, the invention relates to three-dimensional metal objects obtainable by the methods of the invention, and to the use of the three-dimensional metal objects as catalysts or catalyst supports.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [Field of the Invention] The present invention relates to an additive manufacturing process, more particularly to indirect stereolithography (SLA) or digital light processing (DLP) for the fabrication of three-dimensional metal objects. The present invention further relates to a slurry for use in said additive manufacturing process, to a three-dimensional metal object obtainable by said additive manufacturing process, and to the use of the obtained three-dimensional metal object as a catalyst or catalyst support.

[0002] [Background of the invention] Additive manufacturing (AM) is the process of combining materials, usually a layer-by-layer process, to produce objects from three-dimensional computer-aided design (CAD) data models. The applications of additive manufacturing processes have expanded rapidly over the past two decades. Additive manufacturing processes include material jetting, material extrusion, direct energy deposition, sheet lamination, binder jetting, powder bed fusion and photopolymerization. All these techniques can be applied to shape ceramic or metal parts starting from (sub)micrometer sized ceramic or metal particles.

[0003] There are essentially two different categories of AM processes: (i) single-step processes (also called "direct" processes), where the three-dimensional object is made in a single operation and the intended geometric shape and material properties of the fabrication are achieved simultaneously, and (ii) multi-step processes (also called "indirect" processes), where the three-dimensional object is made in two or more steps, where the first step typically results in the basic geometric shape and the second step integrates the fabrication with the intended material properties.

[0004] US Patent No. 6,117,612 discloses an example of a layer-by-layer indirect AM process for the fabrication of ceramic and metal articles. US Patent No. 6,117,612 discloses photocurable resins containing ceramic particles and having a solids loading of greater than 40 vol% and a viscosity of less than 3000 mPa·s, and their use in the multi-layer fabrication of green ceramic parts using stereolithography. The photocurable resins may also contain sinterable metals.

[0005] WO 03 / 092933 discloses a method for fabricating porous titanium 3D-articles, comprising pressing a powder mixture containing titanium powder and 0.01-10 wt% titanium hydride into a predetermined form, and then sintering the pressed powder mixture. The powder mixture may include an organic binder. WO 03 / 092933 does not disclose AM techniques or photopolymerization.

[0006] US 2015 / 337423 discloses metal or metal alloy particulates coated with nanoparticles of metal hydride or metal alloy hydride as sintering aids. The particulates are characterized by an average particle size between about 1 micron and about 1 millimeter, and the nanoparticles are characterized by an average particle size of less than 1 micron. US 2015 / 337423 describes solid articles containing the coated particulates fabricated by an AM technique selected from laser melting and electron beam melting. These AM techniques do not use photopolymerization.

[0007] The present invention relates to a layer-by-layer indirect AM process that utilizes a sacrificial binder material to shape metal-containing particles into a three-dimensional metal object. The binder material is obtained using photopolymerization of a polymerizable resin and a photoinitiator contained in a slurry that also contains metal-containing particles. The binder material is removed in a subsequent "debinding" step. Examples of processes according to the present invention are indirect stereolithography (SL or SLA), digital light processing (DLP) and Large Area Maskless Photopolymerization (LAMP).

[0008] It is essential for the layer-by-layer indirect AM process that the cure depth of the slurry be equal to or greater than the thickness of each layer so that the interface between the layers is sufficiently cured to provide a three-dimensional object containing a binder with sufficient mechanical strength. Therefore, the penetration depth of the energy radiation used to initiate the polymerization reaction via the photoinitiator must be greater than the thickness of the layer.

[0009] The technical background regarding the depth of cure in stereolithography processes for the manufacture of ceramic objects is described in the prior art. In this respect, reference can be made to J. Deckers et al., Additive manufacturing of ceramics: A review, J. Ceramic Sci. Tech., 5 (2014), pp. 245-260; M. L. Griffith and J. W. Halloran, Freedom fabrication of ceramics via stereolithography, J. Am. Ceram. Soc., 79 (1996), pp. 2601-2608; J. W. Halloran et al., Photopolymerization of powder suspensions for shaping ceramics, J. Eur. Ceram. Soc., 31 (2011), pp. 2613-2619; and M. L. Griffith and J. W. Halloran, Ultraviolet curing of highly loaded ceramic suspensions for stereolithography of ceramics, manuscript for the Solid Freeform Fabrication Symposium 1994. These references describe relatively shallow cure depths with highly loaded ceramic particle slurries.

[0010] The depth of cure depends, among other things, on the type of resin, the type and concentration of photoinitiator, the energy radiation dose used to initiate the polymerization reaction via the photoinitiator, and the type and volume fraction of particles. The depth of cure is highly dependent on the scattering of energy radiation by the particles, the volume fraction of the particles, and the absorption of energy radiation by the particles. The difference in refractive index between the particles and the medium carrying the particles, e.g., a photocurable resin with a photoinitiator, can reduce the depth of cure, for example, since scattering is inversely proportional to the square of the difference in refractive index. In this regard, see M.L. Griffith and J.W. Halloran, Freedom fabrication of ceramics via stereolithography, J.Am.Ceram.Soc., 79 (1996), pp. 2601-2608.

[0011] The refractive index n of photocurable resins is typically between 1.3 and 1.7, e.g. 1.5. Many metals have refractive indices very different from 1.5. This means that the depth of cure in slurries containing metal particles is limited by the scattering of energy rays.

[0012] The absorption of energy rays by a particle is related to the imaginary part of the particle's extinction coefficient or refractive index κ. For energy rays with wavelengths between 100 and 800 nm, i.e., a spectrum covering ultraviolet, visible, and infrared light, many (pure) metals have a high extinction coefficient or complex refractive index κ.

[0013] Thus, the cure depth in high loaded metal particle slurries, like high loaded ceramic particle slurries, is often shallow, which limits the applicability of stereolithography or related methods for the production of three-dimensional metal objects.

[0014] The present invention seeks to provide an improved method for the additive manufacturing of three-dimensional metal objects based on indirect stereolithography or related methods, in particular, the present invention seeks to provide a method for the additive manufacturing of three-dimensional metal objects with increased depth of solidification based on indirect stereolithography or related methods.

[0015] [Summary of the Invention] The inventors have found that the above object can be achieved by an additive manufacturing method, in which a slurry containing a mixture of a polymerizable resin, one or more photoinitiators, and a metal-containing compound containing metal particles and one or more metal precursors is used, and a three-dimensional object is built up layer by layer and then processed into the intended three-dimensional metal object. The inventors have established that many metal precursors have a refractive index n for a given wavelength of energy radiation that is closer to the refractive index of the polymerizable resin than the refractive index of the corresponding metal. Moreover, many metal precursors have a lower extinction coefficient or complex refractive index κ for a given wavelength of energy radiation than the corresponding metal. Thus, slurries containing such metal precursors have increased penetration and greater depth of cure for energy radiation of said wavelength compared to slurries containing only the corresponding metal particles.

[0016] Although all the metal particles of the slurry can be replaced by metal precursors, such an approach may result in a highly porous metal object with limited mechanical strength after removing the organic binder and then converting the metal precursor or precursors to the corresponding metal. Subsequent sintering of such highly porous metal objects may lead to significant shrinkage, which may result in defects in the final three-dimensional metal object. The inventors have found that by using a slurry comprising a mixture of a polymerizable resin, one or more photoinitiators and a metal-containing compound, the mixture comprising metal particles and one or more metal precursors, an improved depth of cure can be achieved and a three-dimensional metal object with sufficient mechanical strength can be obtained.

[0017] As a result, the present invention provides an energy radiation curable slurry for additive manufacturing of three dimensional metal objects, said slurry comprising, by weight of the slurry: a) 2-45 wt% polymerizable resin; b) 0.001 to 10 wt % of one or more photoinitiators; c) a mixture of 55-98 wt% metal-containing compounds; wherein the mixture of metal-containing compounds comprises, based on the weight of the mixture, 5-95 wt. % metal particles and 5-95 wt. % one or more metal precursors.

[0018] In a second aspect, the present invention provides an additive manufacturing method for producing a three-dimensional metal object, said method comprising: a) providing a CAD model of a three-dimensional metal object, said CAD model dividing the object into layers and dividing the layers into voxels; b) applying a first layer of an energy radiation curable slurry as defined above, as the layer to be processed, onto the target surface; c) scanning the voxels of the first layer of energy beam curable slurry with an energy beam according to a CAD model to polymerize the polymerizable resin of the energy beam curable slurry into an organic binder; d) applying a next layer of the energy radiation curable slurry as defined above as a layer on top of the first layer; e) scanning the voxels of the next layer of energy beam curable slurry with an energy beam according to the CAD model to polymerize the polymerizable resin of the energy beam curable slurry into an organic binder; f) repeating steps (d) and (e), each time with a subsequent layer being applied over the previous layer, to produce a green body; g) removing the organic binder from the green body of step (f) to obtain a Brownian body; h) optionally converting any remaining metal precursors of the Brownian body of step (g) to the corresponding metal. Includes.

[0019] The invention further provides a three-dimensional metal object obtainable by the method according to the invention. Although it is also possible to produce three-dimensional metal objects from metal powders, for example using selective laser melting or electron beam melting, the three-dimensional metal objects according to the invention differ from those produced using state-of-the-art techniques in the better performance of the object due to the obtained stress-free, very uniform and fine microstructure.

[0020] In another aspect, the invention relates to the use of the resulting three-dimensional metal objects as catalysts or catalyst supports.

[0021] [Definition] The term "indirect stereolithography" as used herein and abbreviated as "SL" or "SLA" refers to a method of building three-dimensional metal objects through layer-by-layer curing of an energy beam curable slurry containing a polymerizable resin, metal particles, and one or more metal precursors using irradiation controlled by computer-aided design (CAD) data from a computer. Indirect stereolithography is typically performed using ultraviolet light to initiate the curing of the polymerizable resin, although the process of "indirect stereolithography" in the context of the present invention can also be performed using other types of energy beams.

[0022] As used herein, the term "green body" refers to a three-dimensional object comprising metal, metal precursors, and hardened organic binder obtained via indirect stereolithography.

[0023] The term "Brown bodies" as used herein refers to three-dimensional objects obtained via indirect stereolithography ("green bodies") from which the organic binder has been removed. Brown bodies can include metals and metal precursors, although metal precursors can also be fully converted to metals.

[0024] As used herein, the term "voxel" means a three-dimensional pixel.

[0025] The term "digital light processing" as used herein and abbreviated as "DLP" refers to an indirect stereolithography method for building three-dimensional metal objects, where each layer is patterned as a whole by exposure to energy radiation in the pattern of a bitmap defined by a spatial light modulator. DLP is also referred to in the art as "large area maskless photopolymerization" and abbreviated as "LAMP". Both terms are considered interchangeable. DLP and LAMP are typically performed using ultraviolet light to initiate the hardening of the polymerizable resin, although the "DLP" and "LAMP" processes in the context of the present invention can also be performed using other types of energy radiation.

[0026] In the context of the present invention, the terms "polymerization" and "curing" are considered synonymous and are used interchangeably. Similarly, the terms "polymerizable" and "curable" are considered synonymous and are used interchangeably.

[0027] The term "sintering" in the context of the present invention should be interpreted as a method of forming a denser metal body from a porous (non-dense) metal body by heat and / or pressure without melting the entire mass. During sintering, the temperature is raised to a sintering temperature, which is below the melting temperature of the body. During this process, atoms at the surface of the porous metal body diffuse across the surface, causing fusion of the metal resulting in a denser material. This diffusion takes place in a temperature range below the melting temperature and is highest when the temperature is close to the melting temperature. It is within the skill of the person skilled in the art to select the appropriate sintering conditions. The metal may contain more types of metal atoms. Thus, the term sintering also includes liquid phase sintering, where at least one but not all of the metal is in a liquid state. [Brief description of the drawings]

[0028] [Figure 1] FIG. 2 shows an EDS spectrum of a tungsten object obtained using a method representative of a method according to the present invention. [Diagram 2] FIG. 1 shows an SEM photograph of a tungsten body obtained using a method representative of the present invention.

[0029] [Detailed Description] In a first aspect of the present invention, there is provided an energy radiation curable slurry for additive manufacturing of three dimensional metal objects, said slurry comprising, by weight of the slurry: a) 2-45 wt% polymerizable resin; b) 0.001 to 10 wt % of one or more photoinitiators; c) a mixture of 55-98 wt% metal-containing compounds; wherein the mixture of metal-containing compounds comprises, based on the weight of the mixture, 5-95 wt % of metal particles and 5-95 wt % of one or more metal precursors. In a preferred embodiment, the mixture of metal-containing compounds comprises, based on the weight of the mixture, 15-95 wt. % metal particles and 5-85 wt. % of one or more metal precursors, more preferably 20-90 wt. % metal particles and 10-80 wt. % of one or more metal precursors.

[0030] In another preferred embodiment, the mixture of metal-containing compounds comprises, based on the weight of the mixture, 45-95 wt.% metal particles and 5-55 wt.% of one or more metal precursors, more preferably 65-95 wt.% metal particles and 5-35 wt.% of one or more metal precursors, even more preferably 80-95 wt.% metal particles and 5-20 wt.% of one or more metal precursors.

[0031] In yet another preferred embodiment, the mixture of metal-containing compounds comprises, based on the weight of the mixture, 5-55 wt. % metal particles and 45-95 wt. % of one or more metal precursors, more preferably 5-35 wt. % metal particles and 65-95 wt. % of one or more metal precursors, even more preferably 5-20 wt. % metal particles and 80-95 wt. % of one or more metal precursors.

[0032] In a preferred embodiment, the mixture of metal-containing compounds comprises, based on the weight of the mixture, 5-95 wt% metal particles and 5-95 wt% of one or more metal precursors, more preferably 15-95 wt% metal particles and 5-85 wt% of one or more metal precursors, even more preferably 20-90 wt% metal particles and 10-80 wt% of one or more metal precursors.

[0033] In another preferred embodiment, the mixture of metal-containing compounds comprises, based on the weight of the mixture, 45-95 wt.% metal particles and 5-55 wt.% of one or more metal precursors, more preferably 65-95 wt.% metal particles and 5-35 wt.% of one or more metal precursors, even more preferably 80-95 wt.% metal particles and 5-20 wt.% of one or more metal precursors.

[0034] In yet another preferred embodiment, the mixture of metal-containing compounds comprises, based on the weight of the mixture, 5-55 wt. % metal particles and 45-95 wt. % of one or more metal precursors, more preferably 5-35 wt. % metal particles and 65-95 wt. % of one or more metal precursors, even more preferably 5-20 wt. % metal particles and 80-95 wt. % of one or more metal precursors.

[0035] Preferably, the energy ray curable slurry as defined above comprises 2.5-25 wt % of polymerizable resin, more preferably 3-15 wt % of polymerizable resin, even more preferably 4-10 wt % of polymerizable resin.

[0036] The metal in the metal particles may be of a single type. In another embodiment, the metal particles comprise a mixture of different metal particles, each particle containing a single type of metal, but different particles may contain different types of metals. In yet another embodiment, the metal particles comprise a mixture of metal alloy particles, each particle containing two or more different metals. In yet another embodiment, the metal particles comprise a mixture of (a) metal alloy particles, each particle containing two or more different metals, and (b) metal particles, each particle containing a single type of metal, but different particles may contain different types of metals. Preferably, the metal particles consist essentially of metal. However, the metal particles may contain up to 5 wt % of non-metallic inorganic components, such as carbon in stainless steel.

[0037] In a preferred embodiment, the metal in the metal particles is selected from the group consisting of beryllium, boron, magnesium, aluminum, silicon, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, and lanthanides including lanthanum, cerium, praseodymium, neodymium, samarium, and actinides including actinium, thorium, protactinium, uranium, neptunium, plutonium, combinations thereof, or metal alloys thereof. Preferred metal alloys are stainless steel, bronze, and brass. Stainless steel is a metal alloy containing iron, nickel, chromium, and 1.2 wt% or less of carbon. Bronze is a metal alloy containing copper, optionally with about 12% tin, and often with the addition of other metals such as aluminum, manganese, nickel, or zinc, and sometimes with the addition of non-metals or semi-metals such as arsenic, phosphorus, or silicon. Brass is a metal alloy made of copper and zinc.

[0038] In a more preferred embodiment, the metal in the metal particles is selected from the group consisting of titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, neodymium, samarium, actinium, thorium, protactinium, uranium, and alloys thereof.

[0039] In an even more preferred embodiment, the metal in the metal particles is selected from the group consisting of titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, molybdenum, hafnium, tantalum, tungsten and metal alloys thereof. A highly preferred metal alloy is stainless steel.

[0040] A metal precursor in the context of the present invention is a chemical entity that contains one or more metal atoms and one or more non-metallic atoms and / or groups and can be converted to the corresponding metal. The non-metallic group or groups can be inorganic or organic in nature.

[0041] The inventors have demonstrated that many metal precursor particles have a refractive index n closer to that of the photocurable resin than that of the corresponding metal for a given wavelength of energy radiation. Moreover, many metal precursor particles have a lower extinction coefficient or complex refractive index κ than the corresponding metal for a given wavelength of energy radiation. The inventors have further demonstrated that many metal precursors that can be molecularly dissolved or colloidally dispersed in the photocurable resin have little effect on the depth of cure. Thus, slurries containing such metal precursors have increased penetration of energy radiation of said wavelength and greater depth of cure compared to slurries containing only particles of the corresponding metal. Examples of the refractive index n and complex refractive index κ of some metal precursors and the corresponding metals at wavelength λ are shown in Table 1.

[0042] [Table 1]

[0043] In one embodiment, the metal precursor takes the form of metal precursor particles. In another embodiment, the metal precursor is molecularly dissolved or colloidally dispersed in the polymerizable resin. In yet another embodiment, the metal precursor comprises a mixture of metal precursor particles and metal precursor molecularly dissolved or colloidally dispersed in the polymerizable resin. Preferred examples of metal precursors that may be molecularly dissolved or colloidally dispersed in the polymerizable resin are organometallic compounds such as metal carboxylates, acetates and formates, and metal alkoxides.

[0044] The metal in the metal precursor may be of a single type. In other embodiments, a mixture of metal precursors containing different metals is used. When the metal precursor is in the form of metal precursor particles, the precursor particles of a single metal may contain metal precursors of different metals.

[0045] The metal in the one or more metal precursors is preferably selected from the group consisting of beryllium, boron, magnesium, aluminum, silicon, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, and the lanthanides, including lanthanum, cerium, praseodymium, neodymium, samarium, and the actinides, including actinium, thorium, protactinium, uranium, neptunium, plutonium, and combinations thereof.

[0046] In a more preferred embodiment, the metal in the one or more metal precursors is selected from the group consisting of titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, neodymium, samarium, actinium, thorium, protactinium, uranium, and combinations thereof.

[0047] In even more preferred embodiments, the metal in the one or more metal precursors is selected from the group consisting of titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, molybdenum, hafnium, tantalum, tungsten, and combinations thereof.

[0048] Examples of metal precursors that can be used in the above defined slurries are selected from the group consisting of metal oxides, metal hydroxides, metal sulfides, metal halides, organometallic compounds, metal salts, metal hydrides, metal-containing minerals, and combinations thereof. Preferred examples of metal precursors that can be used in the above defined slurries are selected from the group consisting of metal oxides, organometallic compounds, metal hydrides, and combinations thereof. Most preferably, the metal precursor comprises a metal oxide.

[0049] Examples of preferred metal oxides are selected from the group consisting of WO3, NiO, MoO3, ZnO and MgO. In a highly preferred embodiment, the metal precursor is the metal oxide WO3.

[0050] Examples of preferred metal hydroxides are selected from the group consisting of Mg(OH)2, 4MgCO3·Mg(OH)2, Al(OH)3, Zn(OH)2, CuCO3·Cu(OH)2, 2CoCO3·3Co(OH)2, Al(OH)(CH3COO)2, Al(OH)(CH3COO)2·H2O and combinations thereof.

[0051] An example of a preferred metal sulfide is MoS2. Examples of preferred metal halides are WCl6 and ZrCl4.

[0052] Examples of preferred organometallic compounds are selected from the group consisting of metal carboxylates, acetates, formates, hydrates thereof, and combinations thereof.

[0053] In a more preferred embodiment, the metal precursor is an organometallic compound or a hydrate thereof selected from the group consisting of Mg(CH3COO)2, Mg(CH3COO)2·4H2O, Fe(COOH)3, Fe(COOH)3·H2O, Al(OH)(CH3COO)2, Al(OH)(CH3COO)2·H2O, Cu(CH3COO)2, Cu(CH3COO)2·H2O, Co(CH3COO)2, Co(CH3COO)2·H2O, Co(CH3COO)2, Zn(CH3COO)2, Zn(CH3COO)2·2H2O, Zn(COOH)2, Zn(COOH)2·2H2O, Pb(CH3COO)2, Pb(CH3COO)2·2H2O, Ti(C5H7O2)4, Ti[OCH(CH3)2]4, and combinations thereof.

[0054] Examples of preferred metal salts are selected from the group consisting of metal carbonates, oxalates, sulfates, hydrates thereof, and combinations thereof.

[0055] In a more preferred embodiment, the metal salt is a metal carbonate, oxalate, sulfate, or hydrate thereof selected from the group consisting of MgCO3, MgC2O4, MgC2O4·2H2O, 4MgCO3·Mg(OH)2, MgSO4·2H2O, MnCO3, MnC2O4, MnC2O4·2H2O, NiCO3, NiC2O4, NiC2O4·2H2O, FeC2O4, FeC2O4·2H2O, CuC2O4, CuCO3·Cu(OH)2, CoC2O4, CoC2O4·2H2O, 2CoCO3·3Co(OH)2, ZnC2O4, ZnC2O4·2H2O, PbC2O4, PbCO3, and combinations thereof.

[0056] Preferred examples of metal hydrides are titanium hydride, zirconium hydride, magnesium hydride, vanadium hydride, tantalum hydride and hafnium hydride. In a more preferred embodiment, the metal precursor is a metal hydride selected from the group consisting of TiH2, MgH2 and TaH5.

[0057] Preferred examples of metal-containing minerals are selected from the group consisting of rutile, ilmenite, anatase, and leucoxene (for titanium), scheelite (tungsten), cassiterite (tin), monazite (cerium, lanthanum, thorium), zircon (zirconium, hafnium, and silicon), cobaltite (cobalt), chromite (chromium), bertrandite and beryl (beryllium, aluminum, silicon), uranite and pitchblende (uranium), quartz (silicon), molybdenite (molybdenum and rhenium), stibnite (antimony), and combinations thereof. The metal contained in the mineral is indicated in parentheses.

[0058] In a highly preferred embodiment, there is provided a slurry as defined above, wherein the metal precursor and the metal particles contain a single metal. An example of this highly preferred embodiment is the slurry as defined above, comprising: a) Ti metal particles and TiH2 metal precursor particles; b) Ti metal particles and titanium(IV) acetylacetonate (Ti(C5H7O2)4) metal precursor; c) Ti metal particles and titanium alkoxide metal precursors such as titanium(IV) isopropoxide (Ti[OCH(CH3)2]4); d) W metal particles and WO3 metal precursor particles; e) Ta metal particles and TaH5 metal precursor particles; f) Hf metal particles and HfH2 metal precursor particles; Includes.

[0059] In another preferred embodiment, the metal precursor and the metal particles contain different metals. An example of this highly preferred embodiment is the slurry defined above, comprising the following: a) stainless steel metal particles and TiH2 metal precursor particles; b) WC metal particles with cobalt oxide precursor particles; Includes.

[0060] The polymerizable resin comprises a monomer, an oligomer, or a combination thereof. In a preferred embodiment, the polymerizable resin comprises a radically polymerizable monomer, an oligomer, or a combination thereof selected from the group consisting of acrylates, (aliphatic) urethane acrylates, vinyl ethers, allyl ethers, maleimides, thiols, and mixtures thereof. In another preferred embodiment, the polymerizable resin comprises a cationically polymerizable monomer, an oligomer, or a combination thereof selected from the group consisting of epoxides, vinyl ethers, allyl ethers, oxetanes, and combinations thereof. Of course, a radically polymerizable resin should be combined with one or more radical photoinitiators, and a cationically polymerizable resin should be combined with one or more cationic photoinitiators.

[0061] The stability and strength of the sacrificial organic binder formed after polymerization of the polymerizable resin can be increased by using cross-linking monomers and / or oligomers that have two or more reactive groups.

[0062] Photoinitiators for radical and cationic polymerization are well known in the art. For a comprehensive overview of photoinitiators, see JPFouassier, JFRabek (ed.), Radiation Curing in Polymer Science and Technology: Photoinitiating systems, Vol. 2, Elsevier Applied Science, London and New York 1993, and JV Crivello, K. Dietliker, Photoinitiators for Free Radical, Cationic & Anionic Photopolymerization, 2nd Ed., In: Surface Coating Technology, Editor: G. Bradley, Vol. III, Wiley & Sons, Chichester, 1999. It is within the skill of the art to match the type of polymerizable resin, the type of energy beam and the photoinitiator or photoinitiators used in the slurry. In a preferred embodiment, the energy beam curable slurry as defined above contains 0.1-4 wt% of one or more photoinitiators.

[0063] It is important that the polymerization of the slurry is controllable when a certain part of the slurry is exposed to energy rays. Moreover, the slurry should have a certain storage stability. For this purpose, the slurry may further comprise 0.001-1 wt%, preferably 0.002-0.5 wt%, of one or more polymerization inhibitors or stabilizers, based on the total weight of the slurry. The polymerization inhibitors or stabilizers are preferably added in an amount such that the slurry is storage stable over a period of 6 months. The slurry is considered storage stable if the viscosity increase over a period of 6 months is less than 10%. Examples of suitable polymerization inhibitors or stabilizers for radically polymerizable resins are phenol, hydroquinone, phenothiazine and TEMPO. Examples of suitable polymerization inhibitors or stabilizers for cationically polymerizable resins are compounds containing alkaline impurities, such as amines, and / or sulfur impurities.

[0064] The particle size and particle size distribution of the metal particles, and of the metal precursor particles when at least a portion of the metal precursor is in particulate form, are important parameters since they affect, among other things, the viscosity of the slurry, the maximum particle loading in the slurry, and the scattering of energy radiation.

[0065] One standard method for specifying the particle size distribution in a particle sample is based on the volume distribution, D 10 , D 50 and D. 90 D 10 is the particle diameter below which 10% of the particle population lies. D 50 is the particle diameter value below which 50% of the population lies and above which 50% of the population lies. D 50 is also known as the median particle size value. D 90 is the diameter value below which 90% of the population lies. Powders with a wide particle size distribution have a diameter of D 10 and D 90 Similarly, a powder with a narrow particle size distribution will have a large difference between the values ​​of D 10 and D 90 There will be a small difference between the values ​​of D 10 , D 50 and D. 90 Particle size distribution, including values, can be determined, for example, by laser diffraction using a Malvern Mastersizer 3000 laser diffraction particle size analyzer.

[0066] Metal particles that can be used in the slurries defined above are of D 3 μm, 6 μm and 9 μm, respectively. 10 , D 50 and D. 90 It is preferred that the particle size distribution be determined by laser diffraction, which can be characterized by a value.

[0067] In a preferred embodiment, the metal particles have a D 90 The diameter of the metal particle is D 10 200% or less larger than the diameter, preferably D 10and even more preferably 150% or less than D 10 D 90 D 10 75% or less than D 10 It may be beneficial for the metal particles to have a narrow size distribution, no more than 50% greater.

[0068] In a preferred embodiment, when at least a portion of the metal precursor is in the form of particles, the metal precursor particles have a particle size and particle size distribution as defined above in the context of metal particles. The particle size and particle size distribution of the metal precursor particles can be selected independently from the particle size and particle size distribution of the metal particles.

[0069] In a more preferred embodiment, the metal precursor particles are smaller than the metal particles. In a highly preferred embodiment, the metal precursor particles have a D of 1 μm, 3 μm and 5 μm, respectively. 10 , D 50 and D. 90 The particle size distribution can be characterized by a particle size distribution determined by laser diffraction.

[0070] A high volume fraction of metal particles and metal precursor particles, when at least a part of the metal precursor or precursors are in particulate form, results in a high viscosity. In this respect, see J. Deckers et al., Additive manufacturing of ceramics: A review, J. Ceramic Sci. Tech., 5 (2014), pp. 245-260, and ML Griffith and JW Halloran, Ultraviolet curing of highly loaded ceramic suspensions for stereolithography of ceramics, manuscript for the Solid Freeform Fabrication Symposium 1994, which describe that the viscosity of suspensions highly loaded with interacting particles has a positive relationship with the volume fraction of the particles. Of course, a suitable rheology of the slurry is necessary to be able to apply thin layers of the slurry on the substrate and on each other. The inventors have found that suitable values ​​for the volume fraction of metal and metal precursor particles and the viscosity of the slurry are as follows:

[0071] The highest possible volume fraction of monodisperse particles is 0.74. The volume fraction of metal particles and of metal precursor particles, in case at least a part of the metal precursor or precursors is in particulate form, in the slurry according to the invention is preferably between 0.10 and 0.70, more preferably between 0.15 and 0.65, even more preferably between 0.30 and 0.60.

[0072] According to ASTM D2196-15(2015), 20℃, 10s -1 ~100s -1 The viscosity of the energy ray curable slurry defined above, measured using a plate-plate rheometer at a shear rate between 0.01 and 50 Pa·s, is preferably between 0.05 and 40 Pa·s, and even more preferably between 0.1 and 35 Pa·s.

[0073] In a second aspect of the present invention there is provided an additive manufacturing method for producing a three-dimensional metal object, said method comprising: a) providing a CAD model of a three-dimensional metal object, said CAD model dividing the object into layers and dividing the layers into voxels; b) applying a first layer of an energy radiation curable slurry as defined above, as the layer to be processed, onto the target surface; c) scanning the voxels of the first layer of energy beam curable slurry with an energy beam according to a CAD model to polymerize the polymerizable resin of the energy beam curable slurry into an organic binder; d) applying a next layer of the energy radiation curable slurry as defined above as a layer on top of the first layer; e) scanning the voxels of the next layer of energy beam curable slurry with an energy beam according to the CAD model to polymerize the polymerizable resin of the energy beam curable slurry into an organic binder; f) repeating steps (d) and (e), each time with a subsequent layer being applied over the previous layer, to produce a green body; g) removing the organic binder from the green body of step (f) to obtain a Brownian body; h) optionally converting any remaining metal precursors of the Brownian bodies of step (g) to their corresponding metals. Includes.

[0074] In a preferred embodiment, the energy radiation used in steps (c) and (e) of the method is actinic radiation. Preferred types of actinic radiation are ultraviolet, visible and infrared. Preferred ultraviolet radiation has a wavelength between 10-380 nm, more preferably between 250-350 nm. Visible radiation has a wavelength between 380-780 nm. As will be recognized by those skilled in the art, the photoinitiator(s) in the slurry must be responsive to the type of energy radiation applied. Matching the photoinitiator with the spectral output of the energy radiation source is within the skill of the skilled artisan.

[0075] The scanning of the voxels of the slurry layer according to the CAD model in steps (c) and (e) may be performed voxel-by-voxel using one or more scanning lasers. Thus, in one embodiment, the additive manufacturing method defined above is an indirect stereolithography (SLA) method for fabricating three-dimensional metal objects, and the scanning of the voxels of the slurry layer according to the CAD model in steps (c) and (e) is performed voxel-by-voxel.

[0076] The scanning of the voxels of the slurry layer according to the CAD model in steps (c) and (e) can also be performed by simultaneously exposing all voxels of the layer to energy radiation through a mask, which defines the pattern of the particular layer to be cured according to the CAD model. Thus, in one embodiment of the present invention, the scanning of the voxels of the slurry layer according to the CAD model in steps (c) and (e) is performed by simultaneously exposing all voxels of the layer to energy radiation through a mask.

[0077] The scanning of the voxels of the slurry layer in steps (c) and (e) can also be performed by exposing all voxels of the layer to the energy beam simultaneously using a spatial light modulator, such as a light engine or beamer, which projects an energy pattern onto the layer so that the voxels are cured according to the CAD model. Thus, in a preferred embodiment, the additive manufacturing method defined above is a Dynamic Light Processing (DLP) method for fabricating three-dimensional metal objects, and the scanning of the voxels of the slurry layer in steps (c) and (e) is performed by exposing all voxels of the layer to the energy beam simultaneously.

[0078] The three-dimensional object comprising the sacrificial organic binder, i.e. the green body obtained in step (f), is subjected to a debinding step (g) in order to remove the organic binder. The binder can be removed by heating the green body typically to a temperature between 90 and 600°C, more preferably between 100 and 450°C. In the debinding step (g), purely thermal and thermochemical processes can take place. The debinding step can be carried out by combustion in an oxidizing or oxygen-containing atmosphere. However, the debinding step is preferably carried out as a pyrolysis step in the absence of oxygen. The debinding step can additionally be carried out in a protective or hydrogen-containing environment.

[0079] Prior to heating the green body obtained in step (f), the green body can optionally be treated with a solvent to separate the green body from the unhardened slurry and / or to extract the extractable organic components. Depending on the solubility of the extractable components, this solvent can be aqueous or organic in nature. Examples of organic solvents that can be used are acetone, trichloroethane, heptane and ethanol.

[0080] Debinding in step (g) may also remove at least some or all of the organic moieties of the organometallic metal precursor. The decomposed organometallic metal precursor may bring reactive metal components to the surface of the metal particles and induce favorable sintering reactions to fabricate Brownian bodies with increased mechanical strength. Thus, the debinding step (g) may in effect be a sintering process, where the metal precursor is converted to the corresponding metal, making optional step (h) unnecessary.

[0081] When metal hydride particles with a low decomposition temperature, such as TiH2 or ZrH2, are used as the metal precursor particles, the debinding in step (g) may result in the decomposition of the metal hydride into hydrogen, free hydride ions, and metal. This metal from the decomposed metal hydride may deposit on the surface of the metal particles and "bond" them together. Thus, the metal hydride particles with a low decomposition temperature may act as a sintering aid for the metal particles during the debinding in step (g). Thus, the decomposition of the metal hydride during the debinding step (g) may make the optional step (h) unnecessary.

[0082] Most metals, such as titanium, chromium, iron, tungsten and molybdenum, undergo oxidation. When such metals are exposed to an oxygen-containing environment, especially at high temperatures, they develop a metal oxide layer, which results in impaired sinterability of the corresponding metal particles. Without wishing to be bound by theory, it is believed that hydrogen and / or liberated hydride ions formed during decomposition of metal hydride particles can provide a reducing environment, and an oxide replacement reaction leads to improved sintering of metal particles with a metal oxide layer. In such cases, there is less need to carry out the debinding step (g) in a protective or hydrogen-containing environment.

[0083] As explained above, if during the debinding step (g) the metal precursors have already completely decomposed to form new metals, the optional step (h) of converting any remaining metal precursors of the Brownian body of step (g) is unnecessary. On the other hand, if the metal precursors do not completely decompose during the debinding step (g) or if the metal precursors remain completely unchanged during the debinding step (g), it is preferred to carry out step (h) in which any remaining metal precursors are converted to the corresponding metals. Thus, in some preferred embodiments, after the removal of the organic binder in step (g), a new metal is formed in step (h) by conversion of the metal precursors to the corresponding metals. This newly formed metal acts as a metal binder for the original metal particles and / or creates more sintering activity, such that a porous Brownian body is formed with improved mechanical strength compared to the corresponding green body.

[0084] The method of conversion in step (h), in which one or more metal precursors are converted to the corresponding metal, depends on the type of metal precursor. This step can be carried out using methods known in the art. It will be recognized by those skilled in the art that if more than one type of metal precursor is present, more than one of the following methods may be required.

[0085] See, for example, the electrolysis or electro-deoxidation process described in WO 99 / 64638. In this process, referred to in the art as the "FFC process", a solid compound, e.g. a metal oxide, is placed in contact with a cathode in an electrolysis cell containing a molten salt. An electrical potential is applied between the cathode and the anode of the cell such that the compound is reduced. The inventors have found that this process can also be used to convert the Brownian metal precursors obtained in step (g) to the corresponding metals. See further the "FFC process" modifications described in WO 01 / 62996, WO 02 / 40748, WO 03 / 048399, WO 03 / 076690, WO 2006 / 027612, WO 2006 / 037999, WO 2006 / 092615, WO 2012 / 066299 and WO 2014 / 102223. The principles of the "FFC Process" can be used to reduce Brownian bodies containing metal precursors such as oxides of beryllium, boron, magnesium, aluminum, silicon, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, and lanthanides including lanthanum, cerium, praseodymium, neodymium, samarium, and actinides including actinium, thorium, protactinium, uranium, neptunium, and plutonium, to the corresponding metals.

[0086] The principles of the "FFC Process" can further be used to reduce Brownian body containing metal precursors in the form of oxides of several metal-containing minerals that may be found in naturally occurring sands and oxide ores, including rutile, ilmenite, anatase, leucoxene, scheelite, cassiterite, monazite, zircon, cobaltite, chromite, bertrandite, beryl, uranite, pitchblende, quartz, molybdenite and stibnite.

[0087] Alternatively, Brownian bodies containing metal precursors in the form of metal oxides can be converted to the corresponding porous metal Brownian bodies by reduction of the metal oxides with hydrogen gas at temperatures between 700 and 800° C. This is the preferred route for metal oxides such as MoO3 and WO3 that volatilize at temperatures above 800° C. It should be noted that the debinding step and the conversion step of the metal oxide Brownian body using hydrogen gas can be combined by increasing the temperature if the debinding step is also carried out in a hydrogen-containing atmosphere.

[0088] The conversion of the Brownian bodies containing metal precursors in the form of metal hydrides into the corresponding metal Brownian bodies can be conveniently carried out using a thermal step. In this respect, see for example the dehydrogenation step in the well-known hydrogenation-dehydrogenation (HDH) process described in US Pat. Nos. 1,835,024 and 6,475,428. In this dehydrogenation step, hydrogen is removed from, for example, titanium, zirconium, vanadium and tantalum hydrides by heating the hydrides under high vacuum. As explained above, this conversion step is only appropriate if the metal hydrides have not yet completely decomposed during the debinding step (g).

[0089] The conversion of Brownian bodies containing metal precursors such as metal hydroxides, metal salts such as metal carbonates and oxalates, and organometallic compounds such as carboxylates, acetates and formates to the corresponding metallic Brownian bodies can be conveniently carried out using a two-step process. In the first step, the metal hydroxides, metal salts, and / or organometallic compounds of the Brownian bodies are thermally decomposed to metal oxides. In this regard, see J. Mu and D. D. Perlmutter, Thermal decomposition of carbonates, carboxylates, oxalates, acetates, formates, and hydroxides, Thermochimica Acta, 49 (1981), pp. 207-218, which discloses the decomposition temperatures of metal carbonates, carboxylates, oxalates, acetates, formates, and hydroxides, and the resulting metal oxides. In the second step, the Brownian bodies containing metal oxides are converted to the corresponding metallic Brownian bodies using the principles of the "FFC process" described above, or by reducing the metal oxides with hydrogen gas at temperatures between 700 and 800°C. As explained above, in the case of organometallic compounds as metal precursors, this conversion step is only relevant if the organometallic compound has not yet completely decomposed to form new metal during the debinding step (g).

[0090] The conversion of Brownian bodies containing metal sulfides and / or metal halides to the corresponding metal Brownian bodies can also be conveniently carried out using a two-step process. In a first step, the metal sulfides and / or metal halides of the Brownian bodies are converted to metal oxides, for example by heating under oxygen-rich conditions. In a second step, the Brownian bodies containing metal oxides are converted to the corresponding metal Brownian bodies using the principles of the "FFC process" described above, or the Brownian bodies containing metal oxides are converted to the corresponding metal Brownian bodies via reduction with hydrogen gas at temperatures between 700 and 800°C.

[0091] Step (h), in which new metals are formed by conversion of the metal precursors to the corresponding metals, results in a porous Brownian body having improved mechanical strength compared to the corresponding green body.

[0092] The mechanical strength of the porous metal brown body obtained in step (g) or step (h) can be further increased by sintering the porous brown body. Thus, in a preferred embodiment, the porous brown body obtained in step (g) if step (h) is not performed or obtained in step (h) is sintered in a following step (i).

[0093] Sintering results in the compaction and solidification of the porous structure of the Brownian body, making it smaller and stronger. Sintering is typically carried out at a temperature below the melting temperature of the metal or alloy. The sintering temperature or range of sintering temperatures typically varies between 0.6 and 0.9 of the melting temperature. The sintering step may involve two or more temperature cycles to avoid thermal shock that may lead to fracture of the three-dimensional metal object.

[0094] If the porous brown body obtained in step (g) or step (h) contains a single metal, the sintering temperature is below the melting temperature of the pure metal.

[0095] If the porous brown body obtained in step (g) or step (h) contains different metals and / or metal alloys, the sintering temperature is below the minimum melting temperature of the pure metal and below the maximum melting temperature of the metal alloy, preferably below the minimum melting temperature of the pure metal and below the minimum melting temperature of the metal alloy.

[0096] In another embodiment, in which the porous brown body obtained in step (g) or step (h) contains different metals and / or metal alloys and the phase diagram of the overall metal composition exhibits a eutectic melting temperature, the sintering temperature is below the eutectic melting temperature.

[0097] In yet another embodiment, where the porous brown body obtained in step (g) or step (h) contains different metals and / or metal alloys and the phase diagram of the total metal composition exhibits a peritectic decomposition temperature, the sintering temperature is below the peritectic decomposition temperature.

[0098] In yet another embodiment, in which the porous brown body obtained in step (g) or step (h) contains different metals and / or metal alloys and the phase diagram of the overall metal composition exhibits one or more peritectic decomposition temperatures and / or one or more eutectic melting temperatures, it is preferred that the sintering temperature is below all of these temperatures.

[0099] It is within the skill of the art to select an appropriate sintering temperature. Melting temperatures of pure metals, melting temperatures of eutectic mixtures of metals, and decomposition temperatures of peritectic mixtures of metals are known in the art. In this regard, reference may be made to MatWeb (www.matweb.com), an online database of material properties.

[0100] Many metals undergo oxidation when exposed to high temperatures. The metal oxide layer thus formed results in impaired sinterability. Moreover, some metal oxides undergo sublimation at temperatures much lower than the sintering temperature. The sintering temperature of pure tungsten is >2000°C. Tungsten oxidizes when in contact with oxygen-containing gases such as air. At temperatures above 600°C, the oxide WO3 is formed. At temperatures above 750°C, WO3 sublimes. The same applies to molybdenum. The sintering temperature of pure molybdenum is >2000°C. If molybdenum is heated in air above 600°C, volatile molybdenum oxides are formed. Therefore, heating above these temperatures in an oxygen-containing environment leads to loss of the metal. Therefore, sintering is preferably carried out in an inert or vacuum environment such as argon, helium or CO2 gas, or in a reducing environment such as under hydrogen or CO gas.

[0101] In a preferred embodiment, the thickness of the first and subsequent layers of slurry applied in steps (b) and (d) is between 5 and 300 μm, more preferably between 6 and 200 μm, even more preferably between 7 and 100 μm, even more preferably between 8 and 50 μm, and most preferably between 9 and 20 μm.

[0102] A third aspect of the invention relates to a three-dimensional metal object obtainable by the method defined above. The three-dimensional metal object according to the invention differs from those produced using state-of-the-art techniques in the better performance of the object due to its stress-free and highly uniform microstructure.

[0103] In one embodiment of the present invention, the metal particles and metal precursors defined above contain only a single type of metal atom, in which case the additive manufacturing method for fabricating three-dimensional metal objects defined above results in a pure metal object, preferably a titanium object or a tungsten object.

[0104] In another embodiment, the metal particles and one or more metal precursors defined above contain two or more types of metal atoms, in which case the additive manufacturing method for fabricating a three-dimensional metal object defined above results in a metal alloy object.

[0105] In a further embodiment, different slurries are applied in different layers, and the metal particles and metal precursors in each slurry comprise different types of metal atoms, in which case the additive manufacturing method for fabricating three-dimensional metal objects defined above results in a composite metal object comprising different layers of pure metal.

[0106] In yet another embodiment, different slurries are applied in different layers, and the metal particles and metal precursors in each slurry contain two or more types of metal atoms, and the metal compositions of the metal precursor particles in the different slurries are not the same, in which case the additive manufacturing method for fabricating three-dimensional metal objects defined above results in a composite metal object comprising different alloys in different layers. Composite three-dimensional metal objects comprising pure metals and alloys are also envisioned.

[0107] A preferred embodiment relates to a three-dimensional metal object obtainable by the method of steps (a) to (g), optionally steps (a) to (h), as defined above.

[0108] Another preferred embodiment relates to a three-dimensional metal object obtainable by the method defined above comprising steps (a) to (g) followed optionally by step (i), the method comprising steps (a) to (i).

[0109] The porous three-dimensional metal objects obtainable by the method defined above may find application in the field of catalysis or may themselves be applied as catalysts. Thus, a fourth aspect of the invention relates to the use of a three-dimensional metal object obtained via the method defined above as a catalyst or catalyst support.

[0110] Thus, the present invention has been described by reference to certain specific embodiments discussed above, it will be recognized that these embodiments are susceptible to various modifications and alternative forms known to those skilled in the art.

[0111] Moreover, to properly understand this document and its claims, it should be understood that the verb "comprise" and its conjugations are used in their open-ended sense, meaning that items following the word are included, but items not specifically mentioned are not excluded. Furthermore, reference to an element by the indefinite article "a" or "an" does not exclude the possibility that there is more than one element, unless the context clearly requires that there is one and only one element. Thus, the indefinite article "a" or "an" normally means "at least one."

[0112] All patent and literature references cited herein are hereby incorporated by reference in their entirety.

[0113] The following examples are provided for illustrative purposes only and are not intended to limit the scope of the present invention in any way. EXAMPLES

[0114] (Comparative Example) The conventional additive manufacturing technique for the production of tungsten objects is selective laser melting (SLM). The grain size of tungsten particles that can be used in SLM is between 20 and 40 μm (Fisher number).

[0115] The resulting tungsten object was analyzed using SLM and had a surface roughness visible to the naked eye.

[0116] (Example) A homogeneous powder mixture of 50 wt% tungsten particles (W) and 50 wt% tungsten oxide (WO3) particles was prepared.

[0117] Tungsten particles were obtained from HC Stark, Germany, were grade HC400, 99.95 wt% pure, and had a Fischer number of 4±0.2 μm.

[0118] Tungsten oxide particles were also obtained from HC Stark, Germany, and were carbide grade milled blue WO3, 99.6 wt% pure, and had a Fischer number of 1.2-1.8 μm.

[0119] The powder mixture was pressed into a compact body, which was heated in a first furnace in a reducing atmosphere consisting of 7% H2 and 93% N2 from 20° C. to 750° C. at a rate of 200° C. / hr, followed by a dwell time of 4 hours at 750° C. The body was then heated at a rate of 200° C. / hr to 900° C., followed by a dwell time of 3 hours at 900° C.

[0120] The thus obtained heated body was sintered in another furnace under a reducing atmosphere consisting of 100% H2 by heating to 1700° at a rate of 20°C / min, followed by a dwell time of 1 hour at 1700°C. The tungsten body was then cooled to ambient temperature at a rate of 25°C / min and subjected to SEM and EDS analysis (JEOL JSM-6010LA).

[0121] FIG. 1 shows the EDS spectrum of the resulting tungsten object, indicating that all of the tungsten oxide was converted to tungsten.

[0122] FIG. 2 shows an SEM photograph of the resulting tungsten body, showing a uniform structure of smaller tungsten grains originating from tungsten oxide and larger grains originating from tungsten.

[0123] The resulting tungsten object had a very uniform structure and a very low surface roughness, much lower than the surface roughness of tungsten objects obtained using SLM.

[0124] The advantageous characteristics of the tungsten body obtained in this example are inherent to those of a tungsten body obtained according to the additive manufacturing method according to the invention, since the chemistry of the metal and the metal precursors is identical. (Appendix 1) 1. An energy radiation curable slurry for additive manufacturing of three dimensional metal objects, said slurry comprising, by weight of the slurry: a) 2-45 wt% polymerizable resin; b) 0.001 to 10 wt % of one or more photoinitiators; c) a mixture of 55-98 wt% metal-containing compounds; wherein the mixture of metal-containing compounds contains, based on the weight of the mixture, 5 to 95 wt % of metal particles and 5 to 95 wt % of one or more metal precursors. (Appendix 2) The energy ray-curable slurry according to Appendix 1, wherein the mixture of metal-containing compounds contains, relative to the weight of the mixture, 45 to 95 wt% of metal particles and 5 to 55 wt% of one or more metal precursors, preferably 65 to 95 wt% of metal particles and 5 to 35 wt% of one or more metal precursors, more preferably 80 to 95 wt% of metal particles and 5 to 20 wt% of one or more metal precursors. (Appendix 3) 3. The energy ray curable slurry according to claim 1 or 2, wherein the metal in the metal particles is selected from the group consisting of oxides of beryllium, boron, magnesium, aluminum, silicon, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, lanthanides including lanthanum, cerium, praseodymium, neodymium, and samarium, and actinides including actinium, thorium, protactinium, uranium, neptunium, and plutonium, combinations thereof, or metal alloys thereof. (Appendix 4) The energy ray curable slurry according to any one of appendixes 1 to 3, wherein the metal in the one or more metal precursors is selected from the group consisting of beryllium, boron, magnesium, aluminum, silicon, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, lanthanides including lanthanum, cerium, praseodymium, neodymium, and samarium, and actinides including actinium, thorium, protactinium, uranium, neptunium, and plutonium, and combinations thereof. (Appendix 5) The energy ray-curable slurry according to any one of Appendices 1 to 4, wherein the one or more metal precursors are selected from the group consisting of metal oxides, metal hydroxides, metal sulfides, metal halides, organometallic compounds, metal salts, metal hydrides, metal-containing minerals, and combinations thereof, and are preferably selected from the group consisting of metal oxides, organometallic compounds, metal hydrides, and combinations thereof. (Appendix 6) 6. The energy ray-curable slurry according to any one of claims 1 to 5, wherein the one or more kinds of metal precursors are metal precursor particles. (Appendix 7) The one or more metal precursors are organometallic compounds selected from the group consisting of metal carboxylates, acetates, formates, hydrates thereof, and combinations thereof, and are preferably Mg(CH 3 COO) 2 , Mg(CH 3 COO) 2 ·4H 2 O, Fe(COOH) 3 , Fe(COOH) 3·H 2 O, Al(OH)(CH 3 COO) 2 , Al(OH)(CH 3 COO) 2 ·H 2 O, Cu(CH 3 COO) 2 , Cu(CH 3 COO) 2 ·H 2 O, Co(CH 3 COO) 2 , Co(CH 3 COO) 2 ·H 2 O, Co(CH 3 CO) 2 , Zn(CH 3 COO) 2 , Zn(CH 3 COO) 2 ·2H 2 O, Zn(COOH) 2 , Zn(COOH) 2 ·2H 2 O, Pb(CH 3 COO) 2 , Pb(CH 3 COO) 2 ·2H 2 O, Ti(C 5 H 7 O 2 ) 4 , Ti[OCH(CH 3 ) 2 ] 4 7. The energy ray-curable slurry according to any one of claims 1 to 6, which is selected from the group consisting of: and combinations thereof. (Appendix 8) The energy ray-curable slurry according to any one of appendix 1 to 6, wherein the one or more metal precursors are selected from the group consisting of titanium hydride, zirconium hydride, magnesium hydride, vanadium hydride, tantalum hydride, hafnium hydride, and combinations thereof. (Appendix 9) The one or more metal precursors are WO 3 , NiO, MoO 3 7. The energy ray-curable slurry according to any one of claims 1 to 6, wherein the metal oxide is selected from the group consisting of ZnO and MgO. (Appendix 10) The mixture of metal-containing compounds includes a single metal, and the metal particles and metal precursors are in the following combination: a) Ti metal particles and TiH 2 Metal precursor particles; b) Ti metal particles and titanium(IV) acetylacetonate metal precursor; c) Ti metal particles and titanium alkoxide metal precursor; d) W metal particles and WO 3 Metal precursor particles; e) Ta metal particles and TaH 5 Metal precursor particles; or f) Hf metal particles and HfH 2 Metal Precursor Particles The energy ray-curable slurry according to any one of claims 1 to 6, which is selected from the following: (Appendix 11) 20℃、10s -1 ~100s -1 The energy ray-curable slurry according to any one of Appendices 1 to 10, having a viscosity of between 0.01 and 50 Pa s, preferably between 0.05 and 40 Pa s, and more preferably between 0.1 and 35 Pa s, measured using a plate-plate rheometer at a shear rate between 0.01 and 50 Pa s, wherein the viscosity is measured according to ASTM D2196-15. (Appendix 12) 1. An additive manufacturing method for fabricating a three-dimensional metal object, the method comprising: a) providing a CAD model of the three-dimensional metal object, the CAD model dividing the object into layers and dividing the layers into voxels; b) applying a first layer of the energy radiation curable slurry according to any one of claims 1 to 11 as a layer to be processed onto a target surface; c) scanning voxels of the first layer of energy beam curable slurry with an energy beam according to the CAD model to polymerize the polymerizable resin of the energy beam curable slurry into an organic binder; d) applying a subsequent layer of the energy radiation curable slurry according to any one of claims 1 to 11 as a layer on top of the first layer; e) scanning the voxels of the next layer of energy beam curable slurry with an energy beam according to a CAD model to polymerize the polymerizable resin of the energy beam curable slurry into an organic binder; f) repeating steps (d) and (e), each time with a subsequent layer being applied over the previous layer, to produce a green body; g) removing the organic binder from the green body of step (f) to obtain a Brownian body; h) optionally converting any remaining metal precursors of the Brownian bodies of step (g) to their corresponding metals. An additive manufacturing method comprising: (Appendix 13) 13. The additive manufacturing method of claim 12, wherein said converting step (h) is carried out, preferably using electro-deoxidation, heating, heating under vacuum, heating followed by electro-deoxidation, reduction with hydrogen gas, or a combination thereof. (Appendix 14) 14. The additive manufacturing method of claim 12 or 13, wherein step (g), if step (h) is not performed, or step (h), is followed by step (i) comprising sintering the brown body of step (g) or (h). (Appendix 15) 15. The additive manufacturing method according to any one of appendixes 12 to 14, wherein the thickness of the first and subsequent layers of the slurry is between 5 and 300 μm, preferably between 6 and 200 μm, more preferably between 7 and 100 μm. (Appendix 16) 16. An additive manufacturing method according to any one of appendixes 12 to 15, wherein the energy rays are selected from the group consisting of actinic type energy rays, preferably ultraviolet rays. (Appendix 17) 17. A three-dimensional metal object obtainable by the additive manufacturing method according to any one of claims 12 to 16. (Appendix 18) 18. Use of the three-dimensional metal object of claim 17 as a catalyst or catalyst support.

Claims

1. 1. An energy radiation curable slurry for additive manufacturing of three dimensional metal objects, said slurry comprising, by weight of the slurry: a) 2 to 45 wt % of a polymerizable resin; b) 0.001 to 10 wt % of one or more photoinitiators; c) 55-98 wt % of a mixture of metal-containing compounds; the mixture of metal-containing compounds comprising, based on the weight of the mixture, 5-95 wt % metal particles and 5-95 wt % one or more metal precursors; The energy ray curable slurry, wherein the one or more metal precursors are organometallic compounds selected from the group consisting of metal carboxylates, acetates, formates, hydrates thereof and combinations thereof, or metal oxides selected from the group consisting of WO3, NiO, MoO3, ZnO and MgO.

2. 2. The energy ray curable slurry according to claim 1, wherein the mixture of metal-containing compounds comprises, based on the weight of the mixture, 45 to 95 wt % of metal particles and 5 to 55 wt % of one or more metal precursors.

3. 3. The energy ray curable slurry according to claim 1 or 2, wherein the metal in the metal particles is selected from the group consisting of beryllium, boron, magnesium, aluminum, silicon, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, lanthanides including lanthanum, cerium, praseodymium, neodymium, and samarium, and actinides including actinium, thorium, protactinium, uranium, neptunium, and plutonium, combinations thereof, or metal alloys thereof.

4. The energy ray curable slurry according to any one of claims 1 to 3, wherein the metal in the one or more metal precursors is selected from the group consisting of beryllium, boron, magnesium, aluminum, silicon, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, yttrium, zirconium, niobium, molybdenum, hafnium, tantalum, tungsten, lanthanides including lanthanum, cerium, praseodymium, neodymium, samarium, and actinides including actinium, thorium, protactinium, uranium, neptunium, plutonium, and combinations thereof.

5. The energy ray curable slurry according to any one of claims 1 to 4, wherein the one or more metal precursors are metal precursor particles.

6. The one or more metal precursors are Mg(CH 3 COO) 2 , Mg(CH 3 COO) 2 ・4H 2 O, Fe(COOH) 3 , Fe(COOH) 3 ・H 2 O, Al(OH)(CH 3 COO) 2 , Al(OH)(CH 3 COO) 2 ・H 2 O, Cu(CH 3 COO) 2 , Cu(CH 3 COO) 2 ・H 2 O, Co(CH 3 COO) 2 , Co(CH 3 COO) 2 ・H 2 O, Co(CH 3 CO) 2 , Zn(CH 3 COO) 2 , Zn(CH 3 COO) 2 ・2H 2 O, Zn (COOH) 2 , Zn(COOH) 2 ・2H 2 O, Pb(CH 3 COO) 2 , Pb(CH 3 COO) 2 ・2H 2 O, Ti(C 5 H 7 O 2 6. The energy ray-curable slurry according to claim 1, wherein the organometallic compound is selected from the group consisting of:

7. The mixture of metal-containing compounds includes a single metal, and the metal particles and metal precursors are in the following combination: d) W metal particles and WO 3 Metal Precursor Particles The energy ray-curable slurry according to any one of claims 1 to 5,

8. 20°C, 10s -1 ~100s -1 The energy ray curable slurry according to any one of claims 1 to 7, having a viscosity of between 0.01 and 50 Pa·s, measured using a plate-plate rheometer at a shear rate of between 0.01 and 50 Pa·s, the viscosity being measured according to ASTM D2196-15.

9. 1. An additive manufacturing method for fabricating a three-dimensional metal object, the method comprising: a) providing a CAD model of the three-dimensional metal object, the CAD model dividing the object into layers and dividing the layers into voxels; b) applying a first layer of the energy radiation curable slurry according to any one of claims 1 to 8 as a layer to be processed onto a target surface; c) scanning the voxels of the first layer of energy beam curable slurry with an energy beam according to the CAD model to polymerize the polymerizable resin of the energy beam curable slurry into an organic binder; d) applying a subsequent layer of the energy radiation curable slurry according to any one of claims 1 to 8 as a layer on top of the first layer; e) scanning the voxels of the next layer of energy beam curable slurry with an energy beam according to the CAD model to polymerize the polymerizable resin of the energy beam curable slurry into an organic binder; f) repeating steps (d) and (e), each time with a subsequent layer being applied over the previous layer, to produce a green body; g) removing the organic binder from the green body of step (f) to obtain a Brownian body; h) optionally converting any remaining metal precursors of the Brownian bodies of step (g) to the corresponding metals. An additive manufacturing method comprising:

10. 10. The additive manufacturing method of claim 9, wherein the converting step (h) is performed.

11. 11. The additive manufacturing method of claim 9 or 10, wherein step (g), if step (h) is not performed, or step (h), is followed by step (i) comprising sintering the brown body of step (g) or (h).

12. 12. The additive manufacturing method of any one of claims 9 to 11, wherein the thickness of the first and subsequent layers of slurry is between 5 and 300 μm.

13. 13. The additive manufacturing method of any one of claims 9 to 12, wherein the energy radiation is selected from the group consisting of actinic type energy radiation.

14. A three-dimensional metal object obtainable by an additive manufacturing method according to any one of claims 9 to 13.

15. 15. Use of the three-dimensional metal object of claim 14 as a catalyst or catalyst support.

Citation Information

Patent Citations

  • Coated powder particles for the fabrication of three-dimensional bodies by layer manufacturing

    JP2006521264A

  • Method for manufacturing three-dimensional molded object, apparatus for manufacturing three-dimensional molded object, and three-dimensional molded object

    JP2017031495A

  • Metallic filled pastes

    US20020176793A1

  • Binder removal in selective laser sintering

    US20040081573A1